2012
DOI: 10.1038/onc.2011.657
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic regulation of S6K1 expression creates a positive regulatory loop in control of breast cancer cell proliferation

Abstract: The 40S ribosomal S6 kinase 1 (S6K1) is an important regulator of cell growth. Expression of S6K1 is often elevated in breast cancer cells. However, the transcriptional mechanism of S6K1 overexpression is not understood. In this report, we demonstrate that estrogen activates expression of S6K1 via Estrogen Receptor (ER) α in ER-positive breast cancer cells. We also show that estrogen acts on the proximal promoter of the S6K1 gene in a mechanism involving the transcriptional factor GATA-3. Finally, we provide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…In addition, RPS6KB1 is a target gene for ER transcription (Maruani et al 2012). S6K2 has recently been brought to light as a potentially important oncoprotein, with fewer essential roles in normal tissue than S6K1, making it an interesting treatment target (Pardo & Seckl 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RPS6KB1 is a target gene for ER transcription (Maruani et al 2012). S6K2 has recently been brought to light as a potentially important oncoprotein, with fewer essential roles in normal tissue than S6K1, making it an interesting treatment target (Pardo & Seckl 2013).…”
Section: Introductionmentioning
confidence: 99%
“…phosphorylated AKT and phosphorylated mTOR) in tumors after treatment, compared with pretreatment levels, was predictive of a better clinical outcome (Generali et al 2008(Generali et al , 2011, suggesting that estrogen via the ER was regulating these pathways, directly or indirectly in vivo. Many preclinical models have shown that estrogen, via ER signaling, at least in part, regulates the activities of PI3K/AKT/mTOR, p38MAPK, and MAPK/ ERK1/2 (Zhang et al 2002, Lee et al 2005, Yu & Henske 2006, Kazi et al 2009, Maruani et al 2012. This suggests that the use of hormonal therapies in combination with the most appropriately targeted kinase inhibitors may be more beneficial at the onset of therapy than application in a sequential fashion.…”
Section: Kinase Overexpression Associated With Sensitivity To Endocrimentioning
confidence: 99%
“…61 S6K1 can directly phosphorylate ERα on Ser167; conversely, ERα activation leads to increased S6K1 expression, resulting in a positive coregulatory loop. 18,19,61 Thus, it appears may play a secondary or indirect role. 19,39 Importantly, this site is associated with tamoxifen resistance.…”
Section: S6k1 In Er-positivementioning
confidence: 99%
“…For that S6K1 expression is maintained in two modes: a basal level of expression, typical of normal cells, and an estrogen/ ERα-dependent specific upregulation. 61 Others have observed estrogen-mediated regulation of RPS6KB1 transcription in ZR-75-1 and MCF7 ER-positive breast cancer cell lines. 62,63 The estrogenic mode of S6K1 upregulation does not seem to be limited to breast epithelia.…”
Section: S6k As a Prognostic And A Therapeutic Target In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation